Analysis Of Toll Gate Traffic Delay Time Using E-Toll System On Waru-Juanda Toll Road - Rhyans Harkanas Anugerah Wicaksana; Sri Wiwoho Mudjanarko (Journal of World Conference (JWC), 2020)
Currently the traffic on the highway is getting crowded, because it filled with so many four-wheeled vehicles. To reduce congestion at the highway then be made to the motorway. But the government's efforts to maximize the use of toll roads to minimize congestion in fact, has not run optimally for payments using the system to pay cash (cash) is less effective. In 2017 PT. Margatama image Surabaya implement E-Toll at the toll booth Waru - Juanda. To find out how the effectiveness of the use of E-Toll system was conducted research to analyze traffic toll gate delay time with the e-toll system on toll roads hibiscus - juanda. Collecting data in this study conducted on Friday at 4:00 p.m. to 20:00 pm and is located at the toll gate Menanggal. The variables used were manual payment system / cash and payment systems using E-toll by noting the number of vehicles entering the toll gate along with the time needed to conduct transactions at toll booths. From the research conducted, the average time delay that is required at the time for using the E-Toll Card was 13.6 seconds / transaction so that they result in queues at toll gates. From these results it can be concluded that the use of E-Toll card is still not effective in reducing congestion at toll booths. The average time delay that is required at the time for using the E-Toll Card was 13.6 seconds / transaction so that they result in queues at toll gates. From these results it can be concluded that the use of E-Toll card is still not effective in reducing congestion at toll booths. The average time delay that is required at the time for using the E-Toll Card was 13.6 seconds / transaction so that they result in queues at toll gates. From these results it can be concluded that the use of E-Toll card is still not effective in reducing congestion at toll booths.